Analysis of village fund efficiency and the variables affecting it in Indonesia - Sutikno; Zulkefly Abdul Karim; Alifah Rokhmah Idialis (Public and Municipal Finance)
Since the reform era, Indonesia has experienced three stages of fiscal decentralization. In the third stage, the focus of the policy shifted to village development by giving authority to manage village funds. However, due to a lack of supervision and inefficient governance, this policy has not been able to improve the quality of rural development. The purpose of this study is to evaluate the level of efficiency of village fund use and analyze the variables that influence it. This study employs data envelopment analysis (DEA) to determine the level of efficiency and binary logistic regression to determine the variables that influence it in 2018 and 2021. The results show an increase in the number of provinces experiencing efficiency in managing village funds. In 2018, 10 provinces (30.30%) were declared efficient, but the remaining 23 (69.70%) were declared inefficient. In 2021, the number of provinces declared efficient increased to 14 (42.42%), while 19 (57.58%) were still considered inefficient. This finding signals that the level of village fund efficiency in Indonesia is still a major challenge toward increasing rural economic growth. The variable that significantly affects the level of efficiency is the level of education of the village head. The lack of human resources who have expertise in village fund management has resulted in low-quality implementation of village development and community empowerment programs.